2010
DOI: 10.1210/en.2009-0814
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor Cell Expansion and Organ Size of Mouse Adrenal Is Regulated by Sonic Hedgehog

Abstract: The adrenal capsule is postulated to harbor stem/progenitor cells, the progenies of which contribute to the growth of adrenocortex. We discovered that cells in the adrenal capsule are positive for Ptch1 and Gli1, genes indicative of responsiveness to the stimulation of Hedgehog (Hh) ligands. On the other hand, Sonic hedgehog (Shh), one of the mammalian Hh ligands, is expressed in the adrenocortex underneath the adrenal capsule, possibly acting upon the Hh-Responsive capsule. To investigate the functional signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(137 citation statements)
references
References 51 publications
5
128
1
3
Order By: Relevance
“…The blockade of Shh function in vivo resulted in deficient Bergmann glia differentiation as well as abnormal development of Purkinje neurons (Dahmane & Ruiz i Altaba 1999). Previous studies also showed that Shh could be expressed in many kinds of cells in the brain (Huang et al 2010), including choroid plexus and Purkinje cells, but in our study, the Shh-positive cells in cerebellum were Bergmann glia. This tiny difference needs to be explained with further investigation.…”
Section: Sonic Hedgehog (Shh) Serves As a Key Molecule For The Differcontrasting
confidence: 85%
“…The blockade of Shh function in vivo resulted in deficient Bergmann glia differentiation as well as abnormal development of Purkinje neurons (Dahmane & Ruiz i Altaba 1999). Previous studies also showed that Shh could be expressed in many kinds of cells in the brain (Huang et al 2010), including choroid plexus and Purkinje cells, but in our study, the Shh-positive cells in cerebellum were Bergmann glia. This tiny difference needs to be explained with further investigation.…”
Section: Sonic Hedgehog (Shh) Serves As a Key Molecule For The Differcontrasting
confidence: 85%
“…Previous studies have demonstrated a key role for SHH signaling in the recruitment of capsular Gli1 + cells to the steroidogenic lineage (Ching and Vilain 2009;King et al 2009;Huang et al 2010), and Shh has been suggested to be regulated by canonical β-catenin signaling in the adrenal system (Drelon et al 2015) and several other developmental systems (Iwatsuki et al 2007;Ahn et al 2010). To test whether this pathway is affected in Rspo3 mutants, we carried out qPCR, immunohistochemistry, and in situ hybridization (ISH) analysis on E16.5 tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Shh in turn signals back to recruit capsular cells to form the adrenal cortex, at least during development. The fact that Shh knockout mice show normal adrenal zonation (Huang et al 2010) while Rspo3 deletion affects ZG identity indicates that Rspo3 must also act through additional, Shh-independent pathways. The dramatic thinning of the entire steroidogenic compartment further supports the model of a ZG-driven adrenal cortex renewal, a concept that has been put forward by Freedman et al (2013).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, lineage tracing showed that the descendants of the downstream activator of the SHH pathway, GLI1, which is only found in the adrenal capsule, also gave rise to differentiated adrenocortical cells (82). Consistent with these findings, conditional deletion of Shh in steroidogenic adrenocortical cells (under the Sf1 promoter) demonstrated marked adrenal hypoplasia, with the adrenal gland being 5-10 times smaller than the wild type but with a normal-sized medulla (83,84). Despite the clear size reduction with a thin capsule, the adrenal gland managed to maintain proper zonal organisation and steroidogenic cell differentiation (84).…”
Section: Adrenal Biology and Adrenocortical Stem/ Progenitor Cells (Amentioning
confidence: 59%